Postoperative Outcomes and Prognostic Factors of High Myopia-Epiretinal Membrane Associated with Retinoschisis after Vitrectomy - Xiao Feng; Xiaohan Yang; Biying Qi; Xinbo Wang; Xijin Wu; Qinlang Jia; Wu Liu (Ophthalmic Research)
Introduction: The outcomes and prognosis of pars plana vitrectomy (PPV) for high myopia-epiretinal membrane (HM-ERM) patients with retinoschisis remains unclear. The aim of this study was to analyze the impact of retinoschisis on the recovery of macular configuration and visual acuity following ERM removal in eyes with HM and to explore the prognostic factors. Methods: A retrospective study of 73 consecutive patients with HM-ERM who underwent PPV with ERM peeling. According to the optical coherence tomography images, eyes were classified into 4 groups: group A without retinoschisis, group B with outer retinoschisis, group C with inner retinoschisis, and group D with both inner and outer retinoschisis. Results: In groups A, B, C, and D, there were 17, 21, 22, and 16 eyes, respectively. Retinoschisis of 44 eyes (74.6%) disappeared postoperatively, including 11 eyes in group B, 20 in group C, and 8 in group D. No correlation was found between retinoschisis resolution and baseline factors. The mean best corrected visual acuity (BCVA) significantly improved at the final follow-up (p < 0.001). The final BCVA was associated with baseline BCVA (p = 0.001), the presence of epiretinal proliferation preoperatively (p = 0.014), and the postoperative integrity of the ellipsoid zone (EZ) (p = 0.001) and interdigitation zone (IZ) (p = 0.008). Conclusions: After surgery, the inner retinoschisis usually resolved completely. Retinoschisis was not the main factor influencing final BCVA. Preoperative BCVA and disruption of EZ and IZ were associated with good visual recovery in long-term follow-up.